Lessons learned: One medical group's dissection and approach to remote patient monitoring services - Gaurav Thakral (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Remote patient monitoring (RPM) has gain popularity over the last two decades. Initially sought after by large hospitals and academic institutions, RPM has shown benefits to patient management at all levels including solo practice. Majority of the companies we identified address two primary diagnosis, hypertension and diabetes. In an analysis of 10 companies we found cost structures varied greatly between vendors while equipment type did not. While there are numerous commonalities between vendors, each vendor differentiated itself through online dashboards and clinical pathways navigations. As the RPM market expands, it is important for physicians to have a structured approach to identifying vendors, selecting appropriate features and contracting with vendors. This article covers cost structures, commonalities and unique aspect of the vendors we reviewed.